2018
DOI: 10.1002/ece3.4181
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of melon aphids Aphis gossypii associated with landscape features

Abstract: Despite increasing evidence that landscape features strongly influence the abundance and dispersal of insect populations, landscape composition has seldom been explicitly linked to genetic structure. We conducted a genetic study of the melon aphid, Aphis gossypii, in two counties of Beijing, China during spring migration using samples from watermelon. We performed aphid genetic analysis using restriction site associated DNA sequencing (2b‐RAD) and investigated the relationship between land cover and the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Indeed, impacts of landscape complexity on the natural enemies of crop pests have been widely studied (Chaplin‐Kramer et al 2011), especially for parasitoid communities (Kruess 2003, Thies et al 2003, Rand et al 2012). However, few studies have been done on the role of landscape composition in conservation biological control in greenhouses (but see Dong et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, impacts of landscape complexity on the natural enemies of crop pests have been widely studied (Chaplin‐Kramer et al 2011), especially for parasitoid communities (Kruess 2003, Thies et al 2003, Rand et al 2012). However, few studies have been done on the role of landscape composition in conservation biological control in greenhouses (but see Dong et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed that there were higher hyperparasitism rates in open greenhouses than in closed ones, indicating that biological control with parasitoids is more likely to be disrupted in open greenhouses by hyperparasitoids coming into the crop from the surrounding environment. This raises the issue of the importance of the surrounding landscape to biological control, as highlighted by Dong et al (2018). Because hyperparasitism may lead to the local collapse of primary parasitoid populations and increases in pest populations (Sullivan and Völkl 1999), one should consider these organisms when planning or applying any biological control program with parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…46 how likely is that insecticide resistance will evolve; Hawkins, Bass, Dixon, & Neve, 2019), and virus 47 transmission dynamics as different genotypes differ in their vector competence (Jacobson & 48 Kennedy, 2013). Evolutionary and ecological factors such as gene flow and distribution of hosts affect 49 genetic variation in populations, which influences the adaptive responses to environmental change 50 and selective pressures (Caprio & Tabashnik, 1992; Davis & Shaw, 2001;Dong, Li, & Zhang, 2018). 51…”
Section: Introduction 41mentioning
confidence: 99%
“…Codling moth ( C. pomonella ) populations in Chile showed a significant but weak genetic differentiation between adults collected in managed and unmanaged orchards, indicating active adult movement between both habitat types 35 . For melon aphids ( Aphis gossypii Glover) it has been shown that genetic diversity of aphid populations on watermelons cultivated in greenhouses was significantly associated with certain landscape elements in two counties in China 36 . In contrast, a limited gene flow between grain aphid ( Sitobion avenae Fabricius) populations colonizing cereal crops as well as uncultivated hosts growing in field margins was detected in an area in Western France 37 .…”
Section: Discussionmentioning
confidence: 99%